2015
DOI: 10.1002/micr.22423
|View full text |Cite
|
Sign up to set email alerts
|

Il10 and poly‐dl‐lactide‐ɛ‐caprolactone conduits in critical size nerve defect bridging—An experimental study

Abstract: Bridging critical nerve defects through fibrin-filled PLC conduits is possible. Although, autologs nerve graft showed superior histological results. Long-term release of IL10 in the conduit did not improve regeneration of critical nerve defects. © 2015 Wiley Periodicals, Inc. Microsurgery 36:410-416, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In addition, the SFI value was determined to track the change in motor function after nerve grafting. Although some limitations of the SFI value have been questioned, the SFI scale is still used to objectively assess and provide sequential information about the recovery of sciatic nerve function after nerve transection injury (Varejao et al ., ), even in very recently published studies (Das et al ., ; Leibig et al ., ; Liu et al ., ). In this study, we noted that the SFI value was significantly larger in the MSC–ECM group than in the scaffold group at 8–12 weeks after nerve grafting, suggesting that BMSC‐derived ECM had promoting effects on motor function restoration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the SFI value was determined to track the change in motor function after nerve grafting. Although some limitations of the SFI value have been questioned, the SFI scale is still used to objectively assess and provide sequential information about the recovery of sciatic nerve function after nerve transection injury (Varejao et al ., ), even in very recently published studies (Das et al ., ; Leibig et al ., ; Liu et al ., ). In this study, we noted that the SFI value was significantly larger in the MSC–ECM group than in the scaffold group at 8–12 weeks after nerve grafting, suggesting that BMSC‐derived ECM had promoting effects on motor function restoration.…”
Section: Discussionmentioning
confidence: 99%
“…There are a large number of reports using critical gap models, including bridging with engineered neural tissue using Schwann cells and dADSCs, 14,15 bridging with collagen tubes and Schwann cell transplantation, 16 bridging with chitosan tubes, 17,18 and bridging with poly(L-lactide-co-ε-caprolactone) tubes. 19,20 A common aspect of these reports is that better nerve regeneration is demonstrated through intervention, by introducing cells and devising structures for bridging, as compared with that in the nonintervention groups. However, in studies comparing results with autologous nerve grafting, reports have indicated that bridging with artificial material is difficult to compare with autologous nerve grafting.…”
Section: Tubulization In the Critical Gapmentioning
confidence: 99%